Osteogenesis imperfecta - Gupte Tejashri; Iyer V; Damle S; Malik N; Halbe A (Wolters Kluwer Medknow Publications, 2006)
Osteogenesis imperfecta is an inherited disorder of the connective tissue. The extreme bone fragility seen in patients suffering from osteogenesis imperfecta pose a series of problems with regard to behavior management and rendering of quality dental treatment. Presented here a case of a four year old child suffering from osteogenesis imperfecta.